An optimization tube design for the tubular moving bed heat exchanger (MBHE) by the analogy with hopper discharge process - Zhihan Li; Weiqin Lu; Tuo Zhou; Yongqi Liu; Yuqiu Zhang (Case Studies in Thermal Engineering)
Tubular moving bed heat exchangers (i.e., MBHE) are widely used to recover waste heat from high-temperature solid granules. However, the stagnant zone and the cavity zone around the heat exchange tube, as well as bridging-and-breaking phenomenon, would bring a significant heat resistance on heat transfer between high-temperature solid granule and tube wall. Experiment and CFD-DEM simulation in this paper verify the similarity of this phenomenon in hoppers and MBHEs. Besides, three kinds of MBHEs using different kinds of tubes are used to study whether the methods used to improve the flow rate of the hopper can also be used to improve the flow stability of the MBHEs, the result shows that the vertical-direction-force between package particles and MBHE tube bundle is reduced by using these new kinds of tubes. Moreover, many cases under different flow velocity in MBHE are studied to prove the universality of the method. This study provides a reference for future research on improving the flow conditions in tubular MBHEs.